Asymmetric Punishment as an Instrument of Corruption Control - Basu, Karna; Basu, Kaushik; Cordella, Tito (World Bank, Washington, DC, 2014)
The control of bribery is a policy objective in many developing countries. It has been argued that asymmetric punishments could reduce bribery by incentivizing whistle-blowing. This paper investigates the role played by asymmetric punishment in a setting where bribe size is determined by Nash bargaining, detection is costly, and detection rates are set endogenously. First, when detection rates are fixed, the symmetry properties of punishment are irrelevant to bribery. Bribery disappears if expected penalties are sufficiently high; otherwise, bribe sizes rise as expected penalties rise. Second, when detection rates are determined by the bribe-giver, a switch from symmetric to asymmetric punishment either eliminates bribery or allows it to persist with larger bribe sizes. Furthermore, when bribery persists, multiple bribe sizes could survive in equilibrium. The paper derives parameter values under which each of these outcomes occurs and discusses how these could be interpreted in the context of existing institutions.